2017
DOI: 10.12816/0038706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Class II Amalgam and Composite Restorations on Periodontal Health of Posterior Teeth : An in Vivo Study

Abstract: Background Periodontal health at the restorative gingival interface continues to represent one of the most difficult challenges. Unfortunately, they only mimic the physical and morphological aspects of teeth, as they are limited by the absence of the 'ideal material' that would provide characteristics similar to the normal tooth structure. Aims To determine the influence of class II amalgam and composite restorative materials on plaque accumulation, gingivitis and periodontal pocket depth. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
3
1
1
Order By: Relevance
“…The scores of various periodontal indices among patients treated with different dental restorations have been reported. Al-Sanjray et al [30] The outcomes of the periodontal parameters reported in the present study of all groups, namely, the PI and GI scores, were higher than all those of previous reports found in the literature. One explanation for such differences might be the different clinical conditions.…”
Section: Discussioncontrasting
confidence: 60%
“…The scores of various periodontal indices among patients treated with different dental restorations have been reported. Al-Sanjray et al [30] The outcomes of the periodontal parameters reported in the present study of all groups, namely, the PI and GI scores, were higher than all those of previous reports found in the literature. One explanation for such differences might be the different clinical conditions.…”
Section: Discussioncontrasting
confidence: 60%
“…These studies showed variation in the degree of plaque accumulation among patients treated with different restorative materials. Alsanjary et al [28] stated that class II amalgam restorations were associated with A recent cross-sectional study by the current investigator [37] evaluated the effect of service life of class II amalgam restorations on periodontal health of a sample of patients with diabetes. The outcomes of the periodontal parameters reported, namely, the ABL, PI, and GI scores, were remarkably higher than those of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Many research studies were found in the literature that evaluates the effect of different restorative dental materials on periodontal health [20,[26][27][28][29][30]. However, no studies were found that appraise the effect of different service life (age) of class II amalgam restoration on periodontal health.…”
Section: Introductionmentioning
confidence: 99%
“…Datele relevate de prezentul studiu sunt în contradicție cu un studiu clinic, realizat de AL-Sanjary SA și Gasgoos SS, care au evaluat indicii de placă și indicii de sângerare ai unui grup de restaurări compozite și ai unui grup de restaurări din amalgam comparate cu dinții omologi din cavitatea orală nerestaurați, deoarece autorii au raportat o creștere a indicilor de placă și de sângerare la grupul de restaurări compozite comparativ cu grupul control [15].…”
Section: Discuţiiunclassified